Konsep Konsumsi Islami: Integrasi Prinsip-prinsip Islam dalam Teori Konsumsi - Nur Alisa; Pipi Arviana; Nur Azizah; Aulia Alwi; Rahman Ambo Masse (TAFAQQUH, 2023)
The earth and everything in it is a mandate from God to humans to be used as well as possible. Consumption is one of the important elements in economic activities. The application of Islamic economic ethics becomes the foundation and provides limits in consumption behavior. The purpose of this study is to understand the basic concepts of Islamic consumption behavior theory and its principles. This research uses qualitative research with a collection method called library research which collects various references that are relevant to the topic of discussion being studied. The results showed that Islamic consumption behavior theory means a concept of economic activity built on the basis of Islamic law. Consumption behavior is a behavior carried out by a person in order to meet needs by spending the value of the benefits of goods/services to achieve satisfaction. Consumption in an Islamic economic perspective provides physical, spiritual, intellectual and material benefits which are realized in the concept of maslahah. The integration of economic principles and theories in consumption activities is expected to create Islamic consumption behavior according to the guidance of Islamic law.